A comparative cost analysis of insecticide-treated nets and indoor residual spraying in highland Kenya. - Guyatt, H; Kinnear, J; Burini, M; Snow, R (2002)
The relative cost of indoor residual house-spraying (IRS) versus insecticide-treated bednets (ITNs) forms part of decisions regarding selective malaria prevention. This paper presents a cost comparison of these two approaches as recently implemented by Merlin, a UK emergency relief organization funded through international donor support and working in the highland districts of Gucha and Kisii in Kenya. The financial costs (cash expenditures) and the economic costs (including the opportunity costs of using existing staff and volunteers, and an annualized cost for capital items) were assessed. The financial cost for IRS was US dollars 0.86 per person protected, compared with 4.21 dollars for ITNs (reducing to 3.42 dollars to the provider assuming cost recovery). The economic cost per person protected for IRS was 0.88 dollars, compared with 2.34 dollars for ITNs. The costs for ITNs were sensitive to the number of nets sold per community group ('efficiency'), as the delivery costs constituted upwards of 40% of the total cost. However, even marked increases in efficiency of these groups could not reduce the costs of ITNs to that comparable with IRS, except if more than one cycle of IRS was needed. The implications of predicted reductions in the cost of insecticide for both IRS and ITNs are also explored. The provision of itemized cost data allows predictions to be made on changes in the design of these programmes. Under almost all design scenarios, IRS would appear to be a more cost-efficient means of vector control in the Kenyan highlands.